2017
DOI: 10.3389/fmicb.2017.01877
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Serotype-Specific Identification of Non-type b Haemophilus influenzae by Loop-Mediated Isothermal Amplification

Abstract: Over the past four decades, the incidence of meningitis caused by Haemophilus influenzae in children has decreased due to widespread vaccination against H. influenzae type b (Hib). The incidence of invasive diseases due to H. influenzae types not included in the vaccines, however, has increased. At present, there are a limited number of diagnostics available to detect non-type b H. influenzae. To address this issue, we developed a rapid, simple, and cost-effective method for detecting serotypes of H. influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Loop-mediated isothermal amplification methods for serogrouping meningococcus and serotyping Haemophilus influenzae have been established ( 9 , 14 , 15 ). However, LAMP methods for pneumococcus serotyping have not yet been available, and some studies have reported the incidence of invasive diseases due to pneumococcal strains that were not included in the vaccines ( 2 , 40 , 41 ).…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Loop-mediated isothermal amplification methods for serogrouping meningococcus and serotyping Haemophilus influenzae have been established ( 9 , 14 , 15 ). However, LAMP methods for pneumococcus serotyping have not yet been available, and some studies have reported the incidence of invasive diseases due to pneumococcal strains that were not included in the vaccines ( 2 , 40 , 41 ).…”
Section: Perspectivesmentioning
confidence: 99%
“…LAMP-based diagnostic assays for S. pneumoniae, H. influenzae , and N. meningitidis have been established ( 9 13 ). The typing assays using LAMP for the detection of N. meningitidis serogroups [A, B, C, W, X, and Y ( 14 )] and H. influenzae serotypes [a, b, c, d, e, and f ( 15 )] were released.…”
Section: Introductionmentioning
confidence: 99%
“…LAMP reactions were not inhibited, or were inhibited only slightly, when using DNA-spiked CSF and blood. PCR is inhibited by biological substances, particularly heparin 30 and other blood components, including haem, leukocyte DNA, and immunoglobulin G 22,31,32 . The LAMP assay can be performed using simple DNA preparation methods because the LAMP reaction more readily tolerates potentially disturbing biological elements (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…LAMP-based diagnostic assays for S. pneumoniae , Haemophilus influenzae , and Neisseria meningitidis in cerebrospinal fluid (CSF) specimens have been established 17–20 . LAMP-based methods for meningococcal typing to detect meningococcal serogroups A, B, C, X, Y, and W 21 , as well as H. influenzae serotypes a, b, c, d, e, and f, have been developed 17,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used DNA detection techniques for meat identification are based on polymerase chain reaction (PCR) such as randomly amplified polymorphic DNA-PCR (RAPD-PCR), restriction fragment length polymorphism-PCR (RFLP-PCR), PCR with species-specific primers, real-time PCR/quantitative PCR (RT-PCR/qPCR), and digital PCR (dPCR) (Alikord et al 2017;Ballin et al 2009;Farag et al 2015). Despite their high sensitivity and specificity, PCR methods have some limitations including their complicated experimentation, the need of a thermal cycler or an additional detection machine, their relatively high cost of reagents and time consumption, and the need of skilled operators (Ali et al 2012;Ckumdee et al 2016;Seetang-Nun et al 2013;Takano et al 2017;Tomita et al 2008). This thus presents an opportunity for developing novel and more efficient approaches for authenticating meat species.…”
Section: Introductionmentioning
confidence: 99%